Wear of diamond in scribing of multi-crystalline silicon - Kumar, Arkadeep; Melkote, Shreyes N. (Journal of applied physics, 2018)
A practical challenge in slicing of low-cost multi-crystalline silicon (mc-Si) wafers by the fixed abrasive diamond wire sawing process is increased wire consumption due to greater wear of the diamond compared to slicing of the more expensive mono-crystalline silicon (mono-Si) wafers. In this paper, we present the results of scribing of mc-Si and mono-Si materials with two conical tip diamond indenters of the same geometry to understand the possible reasons for increased diamond wear in cutting of multi-crystalline silicon. Specifically, the scribing forces and the diamond indenter wear produced in scribing of the two silicon materials are analyzed. The results show that the forces generated in scribing of mc-Si are higher than in scribing of mono-Si. The higher forces in scribing of mc-Si are consistent with the corresponding higher tip radius of curvature (due to wear) of the diamond indenter compared to the tip radius produced in scribing of mono-Si. Scanning electron microscopy and confocal microscopy of the diamond indenters show that wear is primarily due to physical micro-fracture and blunting of the diamond. Raman spectroscopy shows evidence of stress-induced phase transformation of the diamond and the formation of compressive residual stress in the diamond. Plausible physical reasons, including the role of material inhomogeneity in mc-Si, for the wear of diamond during scribing are given.